QUALIDADE DE VIDA DE MULHERES COM CÂNCER DE MAMA - Souza, Marina M. d.; Santo, Caroline C. D.; Kolankiewicz, Adriane C. B.; Loro, Marli M.; Rosanelli, Cleci d. L. S. P. (Salão do Conhecimento, 2013)
Resumo